Relación entre suicidio y trastorno del espectro autista: una revisión aplicada - Flores Julca, Lelaina Yenli (2023)
The present research seeks to study the relationship between suicide and Autism Spectrum Disorder (ASD) in adolescents, young people and adults who meet such diagnosis, through an applied review. The Scopus database was queried under the PRISMA guidelines, and inclusion criteria and search strategies were defined to analyze 10 scientific articles (Urrutia & Bonfill, 2013). The results show a positive and significant relationship between ASD and suicide, since people with more severe ASD traits (especially social difficulties) have a greater presence of suicide risk; as the limited ability to express emotions, which contributes to the appearance of moods that can generate suicidal ideation. Likewise, it is shown that the interaction between the environment and the traits of the ASD also influence as a factor. For example, the rejection that causes isolation leads them to camouflage their characteristics in order to be accepted, discover a mistaken identity and, consequently, a predisposition to suicide. Finally, the limitations are disclosed, such as the low amount of research on the relationship between the variables, which suggests that exploration for future evaluations and treatments could possibly reduce risk factors.